THE IMPACT OF THE TAX STRATEGY ON TAX COMPETITION AND INVESTMENTS - Surik Nairi, Sargsyan (IJRDO - Journal of Business Management, 2017)
The international tax competition is an integral component of the modern world economy. The tax policy pursued by various states to attract foreign investment, tax base and other opportunities to increase tax revenues often goes beyond rationality and leads to unfair competition. The implementation of effective tax strategy aimed at attracting effective investments is one of the most important tasks of Armenia's current economic routine, which successfully depends on future economic stability and tax competitiveness in the international economic field.